Standardized data sets of the atmospheric and oceanographic observations gathered during MARIA S. MERIAN cruise MSM114/2 (ARC) - Laura Köhler; Dariusz B Baranowski; Michał Brennek; Michał Ciuryło; Lennéa Hayo; Friedhelm Jansen; Daniel Kepski; Stefan Kinne; Beata Latos; Bertrand Lobo; Tobias Marke; Timo Nischik; et al. (PANGAEA, 2024)
The ship campaign MSM114/2 (ARC) with the German research vessel Maria S. Merian took place from 22 January to 23 February, 2023. The campaign started in Mindelo, Cape Verde, and ended in Punta Arenas, Chile. During the campaign, the Intertropical Convergence Zone (ITCZ) was completely crossed three times at an almost constant longitude of 23W yielding three profiles of the ITCZ. Afterwards, a storm was passed in the Roaring Forties, in the South Atlantic. Here, we present a series of standardised data sets of the atmospheric and oceanographic observations gathered during the ARC campaign.